Efektivitas Bahan Ajar Pragmatik Berbasis Experential Learning untuk Meningkatkan Kesantunan Berbahasa Mahasiswa - Dian Ramadan Lazuardi; M. Syahrun Effendi; Deserli Pajarada Wulan Rahmadan; Reza Mareta Permata Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the effectiveness of Pragmatics teaching materials based on experiential learning. The method used is an experiment with a pretest-posttest design with control group research design. Data collection uses interviews and tests. The research population was students of the Indonesian Language and Literature Education Study Program, semester III of the 2023/2024 academic year who took Pragmatics. The samples in the research were classes A and B. Research sampling was carried out using the intact group technique which resulted in class A as the experimental class and class B as the control class. Data analysis techniques to determine the effectiveness of experiential learning-based Pragmatics teaching materials are carried out by analyzing pretest and posttest class learning outcomes using N-gain scores. Next, to determine the increase in language politeness in the control and experimental classes, a t-test was carried out using the SPSS program. The calculation obtained is that if the sig(2-tailed) value is <0.05, it can be said that students' language politeness has increased, there is a difference in the average language politeness of the experimental and control classes. The research results show that Pragmatics teaching materials based on experiential learning to improve students' language politeness based on the n-gain score and n-gain score percent are effective to use. Based on the independent samples test output table, it is known that the Sig. (2-tailed) is 0.000 < 0.05, thus there is a significant difference in effectiveness in the control and experimental classes after using Pragmatics teaching materials based on experiential learning. So it can be concluded that students' language politeness increases after using Pragmatics teaching materials based on experiential learning.